1968
DOI: 10.1083/jcb.37.3.633
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modulations of Plasmalemmal Vesicles

Abstract: Structural modulations affecting a small fraction of the population of plasmalemmal vesicles of vascular endothelia are described. They include forms which are apparently produced by the fusion of the vesicular membrane with the plasmalemma and by the successive elimination of the layers of the two fused membranes. Such modulations are assumed to represent stages in the discharge process of vesicular contents. Other forms, characterized by their flask shape and elongated neck, are assumed to represent stages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
200
1
4

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(213 citation statements)
references
References 27 publications
8
200
1
4
Order By: Relevance
“…Judged by its magnitude and importance for the underlying tissues, a critical function of the endothelium is to mediate the fluid and solute exchanges between the blood plasma and the interstitial fluid, in short microvascular permeability. Although the molecular mechanisms underlying this function are still largely unknown, several endothelial specialized subcellular structures have been involved in these processes: caveolae, transendothelial channels (TEC), fenestrae, sinusoidal gaps, vesiculo-vacuolar organelles (VVOs), and intercellular junctions (for reviews see Palade, 1991;Michel and Curry, 1999;Dvorak and Feng, 2001;Bendayan, 2002;Stan, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judged by its magnitude and importance for the underlying tissues, a critical function of the endothelium is to mediate the fluid and solute exchanges between the blood plasma and the interstitial fluid, in short microvascular permeability. Although the molecular mechanisms underlying this function are still largely unknown, several endothelial specialized subcellular structures have been involved in these processes: caveolae, transendothelial channels (TEC), fenestrae, sinusoidal gaps, vesiculo-vacuolar organelles (VVOs), and intercellular junctions (for reviews see Palade, 1991;Michel and Curry, 1999;Dvorak and Feng, 2001;Bendayan, 2002;Stan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Based on electron microscopy (EM) studies, the SDs of caveolae, TEC and VVOs and the FDs have the same morphology: thin (5-7 nm) protein barrier provided with a central density or "knob" (Palade and Bruns, 1968;Palade, 1969a, 1969b). The FD has an octagonal symmetry (Maul, 1971;Bearer and Orci, 1985), being constituted of radial fibrils starting at the rim and interweaving in a central mesh (Bearer and Orci, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Horseradish peroxidase (HRP),`for instance, when introduced into the general circulation, appears rapidly in cytoplasmic vesicles of lymphatic endothelium (45). Parallel evidence, both structural (7,27) and functional (28), supports the view that vesicles subserve a transport function across blood vascular endothelium.…”
mentioning
confidence: 95%
“…In thin sections of stimulated mast cells, granule membranes often contact the plasma membrane at sites where the intervening cytoplasm has been expressed (7,21), forming what Palade and Bruns (25) termed a "pentalaminar figure ." The occurrence of these structures in many types of secretory cells during exocytosis has suggested that they are a preliminary stage in membrane fusion (2,24,29,30) .…”
mentioning
confidence: 99%